HISTORY AND MODERNITY OF POETRY AS : A Reference Of The Modern Poem In Iraq - Reza Mubarak, muhamad (ALBAHITH ALALAMI, 2022)
One of the most important intellectual issues, which receive attention is the issue of modernity, it has occupied the scholars of all time. However, modern poetry used to have special care in Iraq and in the Arab countries .. it is not strange that the concept of modernity is linked to history .. or having history as the most important dimension of its dimensions .. because Arab poetry is historical and it is moving into an area of ​​the past that is still active in terms of language and literary image .. When some poets found that changing and modernizing poetry became a necessity of evolution, and one of the fundamentals of modernization, the cultural impact did not respond to the desire of poets, and their impulse in modern poetry collides with the power of the inherited and its attachment to the mind and conscience ..  and the moral taste was built on the basis of rhythm, which are difficult to change or tamper with its forms .. but the change became a reality, and without it, the movement of poetry will stop, and will diminish its performance. Perhaps questions raised significantly about the development of the poem in Iraq, whether it benefited from the fiftieth achievement or drifted away from it. Or after we saw the pride brought by Sayab, Nazik and Bayati .. for some it’s just the beginning that must be overcome quickly. The change in the level of poetry can not be separate from a change in terms of thought in general or philosophically. And it must be within the system of evolution that includes social and linguistic studies. Or progress in terms of culture in general, or the evolution in the forms of individual and social awareness, or change in the perception of history and the past and the relationship with the aspiration to the future.Main results:There is an Iraqi tendency towards renewal and modernization, in all aspects of life, especially literary and poetic renewal, as the calls for poetic modernity in the fifties started from Iraq and Baghdad specifically. Any project for renaissance or change should start from the land of Iraq specifically, this land is able to renew itself at all times. It is able to adopt a real basis for modernizing the intellectual and social level as it grew up in the land of Iraq. Any incoming cultural, gnostic or political project cannot be imposed on Iraq if it does not find a basic place in its territory. This does not mean stubbornness and refusal to interact with the other, but it means that the original human thought, can find a natural response in a land that embraced the human idea ..  Iraq is a land that sponsored laws and interacted with thought in the most beautiful form, in its different civilization cycles, the basic ideas of freedom, democracy and human rights must find a foundation in the vast land of Iraq.